Do Radicalized Minors Have Different Social and Psychological Profiles From Radicalized Adults? - Oppetit, Alice; Campelo, Nicolas; Bouzar, Laura; Pellerin, Hugues; Hefez, Serge; Bronsard, Guillaume; Bouzar, Dounia; Cohen, David (Frontiers in Psychiatry, 2019)
Introduction: Radicalization is a major issue in Western societies. Supposedly, there is no predefined pathway leading to radicalization. However, youth appears to be at risk for radicalization. The aim of this study was to compare the social and psychological profiles of radicalized minors and radicalized adults. Methods: This cross-sectional study is based on the first large prospective sample of young French individuals (N = 150) who aimed to join the Islamic State (IS) between 2014 and 2016. This sample included 70 adolescents (mean age 15.82 years old, SD 1.14) and 80 young adults (mean age 23.32 years, SD 4.99). We compared the two groups on their sociodemographic and psychological characteristics. Results: Radicalized minors and radicalized adults have different profiles and follow different paths in the radicalization process. Among the group of minors, there are significantly more female subjects (81.4% versus 55.0%, adj. p = 0.007) and more self-harm history before radicalization (44.3% versus 16.2%, p <0.001). In addition, there are significantly less attempts to radicalize the entourage (24.3% versus 50.0%, adj. p = 0.007), and a tendency to show less cases of radicalization among the entourage (32.9% versus 52.5%, adj. p = 0.075) and less radicalization through physical encounter (45.7% versus 65%, adj. p = 0.082). Discussion: Overall, radicalized minors appear to be more psychologically vulnerable individuals than radicalized adults. These differences highlight the importance of tailored interventions in order to prevent radicalization among vulnerable adolescents.